5 Linking 4D flow MRI and molecular data in bicuspid aortic valve aortopathy: Segmental differences across the aortic circumference. (1st November 2021) - Sophocleous, Froso; Garate, Estefania de; Bigotti, Giulia; Anwar, Maryam; Garcia, Eva Jover; Chamorro-Jorganes, Aranzazu; Rajakaruna, Cha; Chivasso, Pierpaolo; Mitrousi, Konstantina; Francesco, Viola de; Wilson, Aileen; Hamilton, Mark; et al.
Abstract : Background: Patients with bicuspid aortic valve (BAV) have an increased incidence of developing ascending aortic (AAo) dilation. The pathogenesis of BAV-aortopathy (genetic vs. hemodynamic) remains unclear. Objectives: To measure changes in molecular markers and MRI-derived wall shear stress (WSS) around the AAo circumference, elucidating possible molecular-haemodynamic interplay. Methods: BAV patients with aortopathy (n=20) were studied prospectively. Aortic tissue was surgically collected (n=15 patients), divided in six circumferential segments ( figure 1 ) and analysed for a) miRNA by Next Generation Sequencing and miRCURY LNA PCR, b) differential protein content by proteomics and c) elastin content and state by histology. Also, 4D MRI scans were acquired (n=11 patients, n=7 controls) and analysed to quantify WSS ( figure 1 ). Dilated (anterior/right) and non-dilated (posterior/left) aortic segments were compared. Results: Five miRNAs were validated as significantly dysregulated markers from segmental comparison in BAV patients with aortopathy: miR-128-3p (p<0.001), miR-210-3p (p<0.001), miR-150-5p (p=0.007), miR-199b-5p (p=0.012) and miR-21-5p (p=0.034). Eight proteins were significantly dysregulated and linked to three of the above miRNAs, showing involvement in vascular endothelial growth factor (p=0.017), hippo signaling (p=0.016) and arachidonic acid (p=0.005) pathways. Decreased elastic fiber levels (p=0.039) and elastic layer thickness (p=0.016) were measured in the dilated segments. Increased WSS and flow-velocity (p=0.001), helical streamlines and asymmetrical flow were observed at the anterior/right wall in asymmetrically and symmetrically dilated patients (the latter showing higher WSS values), compared to controls ( figure 2 ). Importantly, a correspondence was noted between the high WSS regions from MRI and the segments with more miRNA dysregulation. Conclusion: This is a novel study merging imaging and basic science in the discovery of local changes across the aortic wall circumference of the most common congenital heart disease. MiRNA dysregulation linked to inflammatory pathways, changes in WSS and aortic wall remodelling were concomitantly observed on the anterior/right wall in BAV patients. Also, distinct molecular and haemodynamic differences between symmetrically and asymmetrically dilated patients were noted, emphasizing the need to further study local changes in the aorta.